Attitude toward the work and its influence on the Individual work performance of employees: Basis for Attitude Management - Abun, Damianus; Ubasa, Alvin Luciano A.; Magallanes, Theogenia; Encarnacion, Mary Joy; Ranay, Frelyn B. (Technium Social Sciences Journal, 2021)
This study aims to determine the effect of the attitude of employees toward work and work performance. To establish a theoretical foundation of the study, related literature was reviewed. The study used descriptive assessment and correlational research design. The data were gathered through questionnaires and the data were interpreted using descriptive and inferential statistics in which weighted mean was used to measure the level of extrinsic and intrinsic work values and work performance. While Pearson r correlation was used to measure the correlation between attitude toward work and work engagement of employees. The study found that overall there is a significant correlation between attitude toward work and work performance. Therefore, the hypothesis of the study is accepted.